End Point Polymerase Chain Reaction for Porcine Detection on Food Product of UIN Sunan Ampel Surabaya Canteen - Rokhim, Saiku; Tyautari, Inggrit; Firmansyah, M. Aliffiyan; Rachmawati, Yuanita (Indonesian Journal of Halal Research, 2021)
Halal food means food that permitted under Islamic law and fulfills about requirements. The absence of information about halal food contained in UIN Sunan Ampel Surabaya (UINSA) campus area causes related research to be carried out. This study aims to determine the porcine DNA contamination on food around UINSA area using molecular technology. Twenty two samples used were foods that contain meat and may contain pork obtained from canteens around UINSA area, analyzed using Polymerase Chain Reaction (PCR) method. The analysis was started with DNA isolation of 22 food samples, electrophoresis, PCR, then visualization gel electrophoresis. Primer gene coding for cytochrome b (cyt b) which produces 149 bp of DNA fragments. The results showed that no porcine contamination in 22 food samples, while the positive control showed a band of 149 bp. End point PCR method potentially to detect porcine DNA contaminants in food products around UINSA. Therefore the food is halal and safe for consumption.